Effect of Laser Emission Parameters on Mechanical and Physical Properties of Cast Pure Titanium - Hayashi, Taro; Watanabe, Ikuya; Kurogi, Tadafumi; Shiraishi, Takanobu; Murata, Hiroshi (Journal of Spectroscopy, 2014)
The objective of this study was to investigate the effect of laser beam parameters on the mechanical and physical properties of cast commercially pure titanium. Dumbbell-shaped test specimens (ISO6871) were cast with ASTM grades 2 and 3 Ti. The cast surfaces were laser-treated with various laser emission parameters (current: 200, 220, and 240 A; spot diameter: 1.0, 1.6 mm; pulse duration: 10, 1 ms) under argon shielding. Tensile testing was conducted at a crosshead speed of 1.0 mm/min. Data of tensile strength and elongation were statistically analyzed using ANOVA/Tukey’s test (α=0.05). Hardness depth profiles were made with cross sections of rod-shaped specimens after laser treatments. Control specimens without laser treatment were also prepared. The laser-treated specimens showed significantly higher tensile strengths than those of control specimen for both grades 2 and 3 Ti. The specimens treated with 1.0 mm spot diameter indicated higher tensile strengths than those treated with 1.6 mm spot diameter for both currents (200 A and 240 A). The laser treatment decreased the subsurface hardness and increased the hardness between 75 μm and 400 μm in depth when compared to the hardness of control specimens. Laser surface treatment for cast commercially pure titanium modified integrity of cast surface and significantly improved mechanical and physical property.